THE INFLUENCE OF SPI, SAP UNDERSTANDING, TRAINING QUALITY, HUMAN RESOURCE QUALITY ON THE QUALITY OF REGIONAL FINANCIAL REPORTS - Fidhatuzahra, Naomi Ikko; Andriani, Sri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This study aims to find out: the influence of the internal control system, understanding of government accounting standards, the quality of training and the quality of human resources on the quality of local government financial statements in Malang City. The data collected by the questionnaire included 88 employees in the preparation of financial statements with purposive sampling. The hypothesis was tested using simple regression analysis and multiple regression analysis. The results of this study show that: (1) the internal control system has a positive and significant effect on the quality of local government financial statements, (2) the understanding of government accounting standards is not proven to affect the quality of local government financial statements, (3) the quality of training has a positive and significant effect on the quality of local government financial statements, (4) the quality of human resources has a positive and significant effect on the quality of local government financial statements, (5) Internal control system, understanding of government accounting standards, quality of training and quality of human resources have a positive effect on the quality of local government financial statements